A nonhydrostatic oceanic regional model, ORCTM v1, for internal solitary wave simulation - H. Huang; P. Song; P. Song; S. Qiu; J. Guo; X. Chen (Geoscientific Model Development, 2023)
The Oceanic Regional Circulation and Tide Model (ORCTM), including a nonhydrostatic dynamics module which can numerically reproduce internal solitary wave (ISW) dynamics, is presented in this paper. The performance of a baroclinic tidal simulation is also examined in regional modeling with open boundary conditions.